Isolation and restoration procedures of distribution system / Mohd Azami A Rani - A Rani, Mohd Azami (2013)
Nowadays, the concern for reliability of power distribution system has been high within consumers and utility. Power system reliability is defined as the performance for power system to supply electricity to consumers which comprises of generation, transmission and distribution system. Power system reliability can be described by two basic functional attributes which are 1) adequacy and 2) security" for consumers. In power system, one of important things for the designers and engineers in designing and modeling a power system is isolation and restoration procedures especially for distribution power system. Isolation and restoration procedures are very important to power distribution reliability in maintaining the availability of power supply. In order to find the reliability of distribution system, a case study has been performed on a two distribution substation radial feeder which consists of 2 substations with 15 load points. For further analysis, it is assumes that there are not the load transfer occurrences in the system.